Cyclophosphamide treatment regulates the balance of functional/exhausted tumor-specific CD8+ T cells - Hanoteau, Aurélie; Henin, Coralie; Svec, David; Bisilliat Donnet, Charlotte; Denanglaire, Sébastien; Colau, Didier; Romero, Pedro; Leo, Oberdan; Van den Eynde, Benoit; Moser, Muriel (Oncoimmunology, 2017)
An important question is how chemotherapy may (re-)activate tumor-specific immunity. In this study, we provide a phenotypic, functional and genomic analysis of tumor-specific CD8+ T cells in tumor (P815)-bearing mice, treated or not with cyclophosphamide. Our data show that chemotherapy favors the development of effector-type lymphocytes in tumor bed, characterized by higher KLRG-1 expression, lower PD-1 expression and increased cytotoxicity. This suggests re-engagement of T lymphocytes into the effector program. IFN-I appears involved in this remodeling. Our findings provide some insight into how cyclophosphamide regulates the amplitude and quality of tumor-specific immune responses.
Keywords: effector function; cyclophosphamide; tumor-specific immunity; exhaustion; CD8+ T cells